Synthesis of silver (Ag) nano/micro-particles via green process using Andrographis paniculata leaf extract as a bio-reducing agent - Chafidz, Achmad; Rusdi, Suharno; Nurrahman, Imam; Haryanto; Kalista Wibowo, Agam Duma; Kusmayadi, Adi; Hartanto, Danang Tri (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
In this work silver nano/micro-particles have been synthesized using sambiloto (Andrographis paniculata) plant extract as a bio-reducing agent. The effects of different plant extract concentrations, AgNO3 precursor concentrations, and reaction time on the synthesized silver nano/micro-particles were investigated. The silver nano/micro-particles samples were then analyzed using UV-Vis spectrophotometer (UV-Vis), X-Ray Diffractometer (XRD), Field Emission Scanning Electron Microscopy (FESEM), Particle Size Analyzer (PSA), and Fourier Transform Infra-Red (FTIR) spectroscopy. The UV-Vis absorbance spectrum of the colloid silver nano/micro-particles exhibited that all samples had absorbance peaks at a wavelength around 450 nm, confirming the formation of silver nano/micro-particles. It was also found that the UV-Vis absorbance peak of the silver nano/micro-particles inversely increased with decreasing AgNO3 solution concentration. Whereas, the higher the sambiloto extract concentration the higher the UV-Vis absorbance peaks. The UV-Vis absorbance peak increased with increasing synthesis time, suggesting that silver nano/micro-particles became more prominent. The UV-Vis absorbance peaks of the silver nano/micro-particles were about 0.0462, 0.0637, 0.0729, and 0.0936 at reaction time of 5, 10, 20, and 40 min, respectively. The XRD analysis result confirmed that the synthesized silver nano/micro-particles were in the form of nanocrystals with a face-centered cubic centered without any impurities. Additionally, the FESEM images showed that the silver nano/micro-particles had the primary particle size of 150-300 nm. There was the formation of some secondary particles with the size of about 0.7-1.5?m due to the agglomeration of primary particles. The particle size distribution analysis further confirmed the presence of primary and secondary particles. Meanwhile, the FTIR analysis confirmed the presence of four main peaks, linked to functional groups in the sambiloto extract and involved in the creation of silver nano/micro-particles.